(untitled) (Eurasian Research Bulletin, 2023)
The research work is based on the data of 47 patients with severe damage of severe diabetic heel syndrome (according to Wagner (1979) IV-V degree) who were examined and treated from 2019 to 2022 in the clinical base of Bukhara State Medical Institute of Bukhara Regional Multidisciplinary Medical Center.